A Multimodal Analysis of H&M Video Commercial “A Magical Holiday” - Birgitta Eifelia Panggaraan Pranata (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
In indirect advertising, an advertisement does not boldly show the products on the video. The object of the study in this thesis is a video advertisement of a clothing line, H&M, consisting a story about a family in the holiday season. This thesis aims to show that commercials of H&M “A Magical Holiday” uses multimodality in order to attract the audience through six modes: linguistic, audio, spatial, oral, visual, and gestural modes. In this study, I analyzed the modes by Multimodal Discourse Analysis by Kress and Leeuwen onto the six modes to analyze the advertisement, using the study by Chan and Chia on modes in multimodality. This research is using qualitative analysis by Schreier (2012) since it deals with the connection between all the semiotic modes to bring the message of the advertisement. I analyzed the data by putting the scenes into 6 tables based on the modes. After that, I analyzed the interrelation between each modes. Based on the analysis, the modes helped the advertisers to convey the real message of the video. Beyond the moral message of the story, the advertisement is a marketing tool to promote their products. Key Words: indirect advertising, multimodal discourse analysis, semiotic modes, H&M